Is Harbor Porpoise ( Phocoena phocoena ) Exhaled Breath Sampling Suitable for Hormonal Assessments? - Anja Reckendorf; Marion Schmicke; Paulien Bunskoek; Kirstin Anderson Hansen; Mette Thybo; Christina Strube; Ursula Siebert (Animals, 2021)
Over the last decades, exhaled breath sampling has been established for laboratory analysis in various cetacean species. Due to their small size, the usability of respiratory vapor for hormone assessments was questionable in harbor porpoises ( Phocoena phocoena ). This pilot study compared three different blow collection devices for their suitability in the field and during laboratory processing: a sterile petri dish covered by a Nitex membrane, as well as sterile 50 mL centrifuge tubes with or without manganese(II) chloride as a stabilizer. Collected exhales varied between three, five or ten, depending on feasibility. Hormones were extracted through an ether mix, followed by centrifugal evaporation and cortisol analysis using an immunoassay. Although close to the lower end of the assay's dynamic range, the ELISA produced results ( n = 110, 0.102–0.937 ng/mL). Hence, a simple 50 mL centrifuge tube was determined as the best suited blow collection device, while three consecutive exhales proved sufficient to yield results. These findings are promising regarding the suitability of exhaled breath as a matrix for future endocrine and immune system-related studies in harbor porpoises. If further advanced, blow sampling can become an important, non-invasive tool for studying and monitoring health, stress levels and diseases in harbor porpoises.